Broadcast Media Service, Weather Reports Management and Public Environmental Affability. An Appraisal by Residents in Select Sahel Sahara States of Nigeria - Akpan Udo Usiere,; Nelson Akpan, (Journal of Environmental Science and Economics, 2025)
Concerns abound over environmental and climatic changes. This study investigated the need for clear messages from the media about weather reports. It has the title: “Broadcast Media Service, Weather Reports Management and Environmental Affability: An Appraisal by Residents in Select Sahel Sahara States of Nigeria”. The objectives were to find out the lucidity of weather reports; the extent of credibility; the utility percentage of weather reports for environmental affability among residents of sub-Sahara states in Nigeria. The scope of work was limited to the Sahel-Sahara region of Nigeria. These are: Borno Yobe, Kano, Katsina, Jigawa, Sokoto, Zamfara, Kebbi, The research was an online survey with the population of 23,682,681 persons and a sample size of 600 persons. The instrument of research was an online questionnaire proportionately distributed to respondents. The media richness and the media dependency theories were applied. The findings showed that majority of respondents do not understand the terminologies in weather forecasts. From 600 respondents, 367 or 61 percent of the residents agreed that the weather reports are not very clear for understanding. A major recommendation is that media presenters of weather reports should apply interpretative simplicity models to break complex meteorological terms for audience and listeners understanding.